(untitled) (Medical Forum Monthly, 2024)
Purpose of study: Antimalarial drug resistance was checked against Plasmodium falciparum in Punjab Pakistan. Study Design: Prospective nonrandomized descriptive study. Place and duration of study: Study was conducted in seven districts “Muzaffargarh, D.G.Khan, Jhang, Sheikhupura, Faisalabad, Lahore and Multan” of Punjab, Pakistan during the transmission season from JulyNovember of 2003 to 2008. Materials and Methods: Out of total positive for P.falciparum 612 (228+192+192) subjects were enrolled for study as per eligibility criteria of World Health Organization (WHO) and in vitro standard test kit was used for study. Differences in proportions and its significance were analyzed by chi-square tests. Result: Resistance (%) to chloroquine was noted higher in males (79.5%) and in females (20.4%). Highest resistance (%) 31.8 was detected in 6-15 years age group. Same resistance (%) trend was observed in basoquine for males (72), females (28.35), for age groups 6-15 years (41.7) and total was 34.8. Sulphadoxine-pyrimethamine found highly effective with only 5.7% resistance. Trend of resistance (%) in male, female and among different age groups was found same in chloroquine and basoquine. Conclusion: Differences among the resistance (%) sulphadoxine-pyrimethamine and chloroquine or basoquine was highly significant (p<0.001) and between basoquine and chloroquine resistance difference was non significant (p>0.177). Male of age group 6-15 years having ≥6000 parasite/l must be treated on priority basis by artesunate combination therapy (ACT). Chloroquine was less effective than sulfadoxine-pyrimethamine (adjusted odds ratio [OR], 6.4; 95% confidence interval [CI], 2.4-17.0; P<.001) and basoquine (adjusted OR, 8.4; 95% CI, 2.0-36.5; P = .004). Chloroquine and sulfadoxine-pyrimethamine were equivalent in efficacy at day 28 (adjusted OR, 1.3; 95% CI, 0.3-7.0; P = .73).